Pembinaan Qolbun Sebagai Inti Dari Pengembangan Kurikulum - Wardiah Aeni (Program studi Keagamaan Islam, 2022)
This article discusses one of the goals of education, namely to educate people. The first step that must be taken before dismantling the oddity of education in Indonesia is to know in advance about the nature of human beings themselves. Many people think that humans have three elements, namely physical elements, intellectual elements, and spiritual elements. There is a part of humans called the heart which is the heart of human control. Based on this, this article will discuss the relationship between the heart and education. This article uses qualitative research methods and the conclusion of this type of research method is in the form of words based on a study of a concept of thought of a character or phenomenon that occurs and is synergized with a theory. This literature research is focused on exploring tarbiyah messages in the verses of the Qur'an, related to the theme of Qolbun education.